Increased Ristocetin-Cofactor in Acute Myocardial Infarction: a Component of the Acute Phase Reaction - Cucuianu, Mircea P; Missits, Ileana; Olinic, Nour; Roman, Stefan (Thrombosis and Haemostasis, 1980)
When compared to the values obtained in healthy normal-weight, normolipemic controls, the plasma level of ristocetin-cofactor (VIII: R-cof.) was found to be much higher in patients with acute myocardial infarction and in postoperative conditions (4–5 days after a major surgical intervention). A lesser increase of VIII: R-cof. was noted in atherosclerotic patients without acute occlusive accidents and no significant changes of this plasma factor could be observed in hyperlipemic subjects without obvious clinical atherosclerosis. Serial studies emphasized a tendency towards normalization of plasma VIII: R-cof. as the acute phenomena of a myocardial infarction subsided. The above mentioned data suggest that the high levels of VIII: R-cof. recorded in myocardial infarction are mainly caused by a systemic acute phase reaction and to a lesser extent by endothelial damage. Delayed clearance of VIII: R-cof. subsequent to a hepatic dysfunction or to a modified pattern of protein metabolism during the above mentioned acute phase reaction might also contribute to the high level of this plasma factor.
Keywords: Myocardial infarction; Acute phase reaction; Ristocetin-cofactor